Effect and mechanism of Tangzhiqing in improving cardiac function in mice with hyperlipidaemia complicated with myocardial ischaemia - Zhihui Song; Rui Chen; Caijun Wang; Guiyun Pan; An Yan; Guinan Xie; Zhihua Yang; Wanying Feng; Yi Wang (Heliyon, 2023)
Purpose: Tangzhiqing formula (TZQ) is a traditional Chinese medicine prescribed to treat lipid metabolism disorders, atherosclerosis, diabetes and diabetic cardiomyopathy. However, some challenges and hurdles remain. TZQ showed promising results in treating diabetes and hyperlipidaemia. However, its effect on and mechanism of action in hyperlipidaemia complicated with myocardial ischaemia (HL-MI) remain unknown. Methods: In this study, a network pharmacology-based strategy integrating target prediction was adopted to predict the targets of TZQ relevant to the treatment of HL-MI and to further explore the involved pharmacological mechanisms. Results: A total of 104 potential therapeutic targets were obtained, including MMP9, Bcl-2, and Bax, which may be related to the apoptosis and PI3K/AKT signalling pathways. Then, we confirmed these potential targets and pathways with animal experimentation. TZQ reduced lipid levels, increased the expression levels of Bcl-2, decreased Bax, caspase-3 and caspase-9 expression levels, and activated the PI3K/AKT signalling pathway. Conclusion: In conclusion, this study provides new insights into the protective mechanisms of TZQ against HL-MI through network pharmacology and pharmacological approaches.